From: pver@nemdev11 (Peter Verthez)
Newsgroups: sci.math
Subject: Lagrange's Inversion Formula
Date: 22 Feb 1996 06:27:05 GMT
I encountered the following remarkable formula in The Art Of
Computer Programming (vol.1) by Knuth. Unfortunately no proof
or hint of proof was given.
Given z = t / f(t) with f(0) not equal to 0
and f(t) analytical around 0
inf
-- 1 (n-1) n n
then t = \ --- g (0) z with g (t) = f(t)
/ n! n n
--
n=0
Does anyone know how to prove this ? Method only is ok, details
are not necessary.
Thanks in advance,
__________________________________________________________________________
Peter Verthez Software Engineer
Email: at work pver@bsg.bel.alcatel.be
at home pver@innet.be
==========================================================================